Alkaline earth-organic frameworks with amino derivatives of 2, 6-naphthalene dicarboxylates: structural studies and fluorescence properties. Issue 46 (29th October 2020) - Diamantis, Stavros A.; Hatzidimitriou, Antonios; Plessas, Alexios K.; Pournara, Anastasia; Manos, Manolis J.; Papaefstathiou, Giannis S.; Lazarides, Theodore
Abstract : We present a series of alkaline earth-organic frameworks based on amino-substituted 2, 6-naphthalene dicarboxylate bridging ligands featuring infinite rod and rarely observed square planar M4 secondary building units (SBUs). Abstract : Alkaline earth metal ion organic frameworks (AEMOFs) represent a relatively underexplored subcategory of metal–organic frameworks (MOFs). In this contribution, we present the synthesis and structural study of the new MOFs 1–8 based on the alkaline earth ions Mg 2+, Ca 2+, Sr 2+ and Ba 2+ and the amino substituted bridging ligands 4-aminonaphthalene-2, 6-dicarboxylate (ANDC 2− ) and 4, 8-diaminonaphthalene-2, 6-dicarboxylate (DANDC 2− ). Compounds 1, 5, 6, 7 and 8 constitute rare examples of three-dimensional MOFs which feature square planar M4 secondary building units (SBUs) surrounded by eight bridging ditopic ligands. The underlying topology of MOFs 1, 5, 7 and 8 conforms to the 4-c pcb net which can be simplified to the 8-c bcu net, while 6 adopts the 4-c lta net which simplifies to the 8-c reo net. To the best of our knowledge these are the first examples of MOFs of their structural types formed by linear dicarboxylates instead of trigonal tricarboxylates or tetrahedral tetracarboxylates. Compounds 2, 3 and 4 also feature three dimensional networks with linear rod-shaped SBUs with the Ba 2+ MOF 3 displaying an sra rod-net and MOFs 2 and 4 showing very complex rod-nets with so far unique topologies. Fluorescence studies revealed that the free ligands exhibit strong blue-green emission displaying considerable positive solvatochromism thereby pointing towards charge transfer excited states involving the shift of electron density from the amino groups to the aromatic core. Correspondingly, the MOFs display ligand based fluorescence with small differences in emission maxima possibly attributable to the difference in the charge density of the metal ions combined with the different environments around ligands in the crystal structures.